Applications of magnetic resonance-guided laser interstitial thermal therapy in disconnective epilepsy surgery - Gaba, Fidelia; Hect, Jasmine L.; Abel, Taylor J. (Frontiers in Neurology, 2024)
Minimally invasive surgical techniques, such as MR-guided laser interstitial thermal therapy (LITT), have emerged as promising alternatives to open disconnective surgeries in drug-resistant epilepsy (DRE). This review synthesizes current literature on the application of LITT for corpus callosal disconnection and functional hemispheric disconnection. Studies highlight LITT's effectiveness for achieving seizure control and functional outcomes, often with reduced complications compared to traditional open procedures. Challenges include technical limitations to achieving total disconnection and adequate assessment of disconnection postoperatively. The literature is largely composed of observational studies and there is a need for rigorous, multi-center trials to establish robust guidelines and improve generalizability in clinical practice. There is also a need for a more robust exploration of how patient-specific factors contribute to response or nonresponse to intervention.